Clinical Pearls and Methods for Intraoperative Motor Mapping. Issue 3 (21st January 2021) - Rossi, Marco; Sciortino, Tommaso; Conti Nibali, Marco; Gay, Lorenzo; Viganò, Luca; Puglisi, Guglielmo; Leonetti, Antonella; Howells, Henrietta; Fornia, Luca; Cerri, Gabriella; Riva, Marco; Bello, Lorenzo
Abstract: Resection of brain tumors involving motor areas and pathways requires the identification and preservation of various cortical and subcortical structures involved in motor control at the time of the procedure, in order to maintain the patient's full motor capacities. The use of brain mapping techniques has now been integrated into clinical practice for many years, as they help the surgeon to identify the neural structures involved in motor functions. A common definition of motor function, as well as knowledge of its neural organization, has been continuously evolving, underlining the need for implementing intraoperative strategies at the time of the procedure. Similarly, mapping strategies have been subjected to continuous changes, enhancing the likelihood of preservation of full motor capacities. As a general rule, the motor mapping strategy should be as flexible as possible and adapted strictly to the individual patient and clinical context of the tumor. In this work, we present an overview of current knowledge of motor organization, indications for motor mapping, available motor mapping, and monitoring strategies, as well as their advantages and limitations. The use of motor mapping improves resection and outcomes in patients harboring tumors involving motor areas and pathways, and should be considered the gold standard in the resection of this type of tumor.